Sosialisasi dan Edukasi Tanaman Obat Keluarga di Desa Sirnaputra Tasikmalaya - Ruswanto Ruswanto; Gatut Ari Wardani; Tresna Lestari; Sindi Lestari; Ahmad Tantowi Jaohari (Universitas Mathla'ul Anwar Banten, 2022)
SOCIALIZATION AND EDUCATION OF HERBAL MEDICINE AT SIRNAPUTRA TASIKMALAYA. Plants have been used as a source of food, clothing, and medicine from the time of our ancestors. Knowledge of medicinal plants and their evolution from forests and yards should receive special consideration. For rural communities to maintain their health, locals often choose this nutrient-rich plant. The benefits include the fact that therapeutic plants are chemical-free, affordable, simple to grow, and safe. The problem is the lack of public knowledge about the benefits and how to mobilize medicinal plants so that land use for TOGA is still rarely found. Based on these problems, the solution offered is in the form of socialization and education activities about family medicinal plants. The activities that have been carried out, can increase the insight and knowledge of the community in the use of plants as medicine and how to use them.